2016
DOI: 10.1094/cchem-03-16-0069-fi
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Nutritional Value, and Health Benefits of Pulses

Abstract: Cereal Chem. 94(1):11-31The United Nations has declared 2016 as the International Year of Pulses. Pulses are narrowly defined as leguminous crops that are harvested as dry seeds. Although some pulse crops are harvested green (e.g., green peas), these are classified as vegetables because the pods are often consumed along with the mature and sometimes immature seeds.Other dried legumes such as soybean and peanut meet the definition of being a leguminous crop that is harvested as dry seeds; however, these crops a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
299
5
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 317 publications
(326 citation statements)
references
References 352 publications
(800 reference statements)
17
299
5
5
Order By: Relevance
“…Lower starch damage in milled field pea than in milled cereal grain is probably due to differences in composition. The total starch content of field pea (30%–49%; Hall et al, ) is lower than total starch contents of most cereals (60%–75%; Delcour & Hoseney, ), while dietary fiber (3%–20%) and protein (14%–31%) are higher in field pea than in cereals (e.g., 2%–3% dietary fiber and 10%–15% protein in wheat; Delcour & Hoseney, ). Therefore, pea starch may be partially shielded during milling by the other seed constituents, resulting in lower starch damage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Lower starch damage in milled field pea than in milled cereal grain is probably due to differences in composition. The total starch content of field pea (30%–49%; Hall et al, ) is lower than total starch contents of most cereals (60%–75%; Delcour & Hoseney, ), while dietary fiber (3%–20%) and protein (14%–31%) are higher in field pea than in cereals (e.g., 2%–3% dietary fiber and 10%–15% protein in wheat; Delcour & Hoseney, ). Therefore, pea starch may be partially shielded during milling by the other seed constituents, resulting in lower starch damage.…”
Section: Resultsmentioning
confidence: 99%
“…Pulses such as field pea ( Pisum sativum L.) contain several nutrients associated with health benefits, including high protein, low lipid, and high dietary fiber contents, a high amylose‐to‐amylopectin ratio, and high antioxidant content (Dahl, Foster, & Tyler, ; Hall, Hillen, & Garden‐Robinson, ). Blending pulse ingredients into cereal‐based products has the potential to improve nutritional profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ray et al () observed that when different pulse species were grown in the same location, lentils accumulated higher concentrations of iron, manganese, selenium, and zinc, whereas beans accumulated higher amounts of nickel, magnesium, and copper. Thus, legumes have a range of mineral profiles that could be adjusted to human diets, depending on regional requirements (Hall et al, ; Wang & Daun, ; Wang, Hatcher, Toews, & Gawalko, ; Zia‐Ul‐Haq et al, ). These studies suggest that utilizing diverse legume populations with high concentrations of micronutrients may be an effective strategy to combat hidden hunger.…”
Section: The Benefit Of Legumesmentioning
confidence: 99%
“…They generally contain more than twice as much more protein than cereal grains. For example, yellow peas have a protein content of 200–250 g kg −1 and lentils of 220–250 g kg −1 . The dietary fiber content of pulse seeds ranges from 140 to 530 g kg −1 , which is also higher than in cereals.…”
Section: Introductionmentioning
confidence: 99%